Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41598-022-24374-4
|View full text |Cite
|
Sign up to set email alerts
|

Survival of people with cystic fibrosis in Australia

Abstract: Survival statistics, estimated using data from national cystic fibrosis (CF) registries, inform the CF community and monitor disease progression. This study aimed to estimate survival among people with CF in Australia and to identify factors associated with survival. This population-based cohort study used prospectively collected data from 23 Australian CF centres participating in the Australian CF Data Registry (ACFDR) from 2005–2020. Period survival analysis was used to calculate median age of survival estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…The ACFDR has borne witness to incremental and more recently transformational improvements in morbidity and outcomes for people with CF during this time. Adults exceeded children in the ACFDR for the first time in 2014 4 ; lung function and nutritional status continue to improve; and in the last 5 years particularly, more substantial improvements have been observed in rates of common infections, a decline in overall hospitalisations, a rapid decline in lung transplantation and a sustained increase in life expectancy 5,6 …”
Section: Challenges Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACFDR has borne witness to incremental and more recently transformational improvements in morbidity and outcomes for people with CF during this time. Adults exceeded children in the ACFDR for the first time in 2014 4 ; lung function and nutritional status continue to improve; and in the last 5 years particularly, more substantial improvements have been observed in rates of common infections, a decline in overall hospitalisations, a rapid decline in lung transplantation and a sustained increase in life expectancy 5,6 …”
Section: Challenges Benefitsmentioning
confidence: 99%
“…Adults exceeded children in the ACFDR for the first time in 2014 4 ; lung function and nutritional status continue to improve; and in the last 5 years particularly, more substantial improvements have been observed in rates of common infections, a decline in overall hospitalisations, a rapid decline in lung transplantation and a sustained increase in life expectancy. 5,6 Registries must evolve with the needs of their populations, and CF registries are an exemplar in this regard. 7 During the COVID-19 pandemic, amid concerns regarding the sudden shift to telehealth, early outcomes published using ACFDR data reported that despite this, overall patient outcomes improved.…”
mentioning
confidence: 99%
“…Improved treatment and management plans have led to increased survival and the need to predict disease outcomes other than lung transplantations or mortality 10 . According to the Australian Cystic Fibrosis Data Register (ACFDR), the survival age has been increasing over time, whereby the median age of death is currently 31 years 11 . Despite this projected increase in median survival age and the discovery of sophisticated therapies, quality of life is still limited due to significant clinical, psychological, psychosocial, and economic burdens 12 .…”
Section: Introductionmentioning
confidence: 99%
“…10 According to the Australian Cystic Fibrosis Data Register (ACFDR), the survival age has been increasing over time, whereby the median age of death is currently 31 years. 11 Despite this projected increase in median survival age and the discovery of sophisticated therapies, quality of life is still limited due to significant clinical, psychological, psychosocial, and economic burdens. 12 With increased life expectancy, predicting the prognosis of the patient's disease, such as progression and severity, is critical to the patient's quality of life treatment options, adherence, and psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…Cystic Fibrosis (CF) is the most common lethal genetic disease in the Caucasian population, with a median age of survival of 54.0 years (1). Death is mainly a result of respiratory failure, which correlates closely to nutritional status (2).…”
Section: Introductionmentioning
confidence: 99%